Absence of Escherichia coli, Listeria monocytogenes, and Klebsiella pneumoniae antigens within inflammatory bowel disease tissues. Issue 9 (September 1998) - Walmsley, R S; Anthony, A; Sim, R; Pounder, R E; Wakefield, A J
Abstract : BACKGROUND: Escherichia coli, listeria, and streptococcal antigens have been found in Crohn's disease tissues. Antibodies to Klebsiella pneumoniae have been found in patients with inflammatory bowel disease and ankylosing spondylitis. The presence of these bacterial antigens in Crohn's granulomas would be of aetiological interest, while their presence in ulcers alone would be more likely to indicate secondary infection. AIM: To investigate inflammatory bowel disease tissues for the presence of these bacteria. METHODS: Formalin fixed, paraffin processed sections from 53 patients (19 ulcerative colitis, 23 Crohn's disease; 11 normal tissues from cancer resections) were studied by immunohistochemistry. Control tissue consisted of normal human small bowel injected submucosally with either E coli, Listeria monocytogenes, Proteus mirabilis, or Klebsiella pneumoniae serotypes K2, 3, 17, 21, 26, 36, and 50, and colonic biopsies from a child with E coli 0114 infection. Tissues were stained by Gram-Twort, and with specific antibodies for E coli (Dako B357), L monocytogenes (Difco 2302-50), and K pneumoniae (Biogenesis 5580-5208) using an immunoperoxidase technique. RESULTS: Positive staining for E coli was observed on the luminal surface epithelium and in ulcers in 35% of Crohn's disease patients, 26% of ulcerative colitis patients, and no normal controls. Superficial staining for L monocytogenes was observed in one case of ulcerative colitis only. Staining for K pneumoniae was observed in one case of ulcerative colitis and one of Crohn's disease. No granulomas, giant cells, or germinal centres stained positively for any of the three bacterial antigens. CONCLUSIONS: These data do not support a primary role for E coli, L monocytogenes, and K pneumoniae in inflammatory bowel disease. The presence of E coli antigens in ulcers suggests secondary infection in these lesions.